The effect of exercise on skeletal muscle fibre type distribution in obesity: From cellular levels to clinical application - Sintip Pattanakuhar (2018)
© 2016 Asia Oceania Association for the Study of Obesity Skeletal muscles play important roles in metabolism, energy expenditure, physical strength, and locomotive activity. Skeletal muscle fibre types in the body are heterogeneous. They can be classified as oxidative types and glycolytic types with oxidative-type are fatigue-resistant and use oxidative metabolism, while fibres with glycolytic-type are fatigue-sensitive and prefer glycolytic metabolism. Several studies demonstrated that an obese condition with abnormal metabolic parameters has been negatively correlated with the distribution of oxidative-type skeletal muscle fibres, but positively associated with that of glycolytic-type muscle fibres. However, some studies demonstrated otherwise. In addition, several studies demonstrated that an exercise training programme caused the redistribution of oxidative-type skeletal muscle fibres in obesity. In contrast, some studies showed inconsistent findings. Therefore, the present review comprehensively summarizes and discusses those consistent and inconsistent findings from clinical studies, regarding the association among the distribution of skeletal muscle fibre types, obese condition, and exercise training programmes. Furthermore, the possible underlying mechanisms and clinical application of the alterations in muscle fibre type following obesity are presented and discussed.